Morpho-physiological and yield performance of grain sorghum genotypes - Ghosh, Shepon Chandra; Akram, Soleh; Ahsan, SM; Asif, Abdulla Al; Shahriyar, Sayeed (Asian Journal of Medical and Biological Research, 2015)
A pot experiment was carried out at the grill house of the Department of Crop Botany, Bangladesh Agricultural University, Mymensingh during the period from December 2013 to April 2014 to study the growth, morpho-physiological, yield and yield contributing characters of twenty sorghum genotypes. The experiment was consisted of twenty genotypes of sorghum viz., BD 700, BD 701, BD 702, BD703, BD704, BD705, BD706, BD707, BD708, BD709, BD710, BD712, BD720, BD721, BD722, BD725, BD726, BD727, BD728 and BD729. The experiment was laid out in a Completely Randomized Design with three replications. The collected data were analyzed statistically and the means were adjudged by Duncans multiple range test at 1% level of probability. Among the genotypes, BD 725 showed significantly the best performance on growth, yield and morphophysiological characters compare to other genotypes at harvest, while BD728 was less efficient among those parameters. As a result, highest plant height (251.20 cm), panicle plant1 (2.83), highest 1000grain weight (27.10 g), highest grain yield (3.58 t ha1), straw yield (16.05 t ha1) and biological yield (19.64 t ha1) was recorded from BD 725 at harvest. However, number of leaves, leaf area plant1 and Leaf area index had also significantly highest (18.33 and 5542.0 cm2 and 2.81, respectively) in BD 725 at 90 days after sowing. BD 725 further recorded the highest growth of cumulative growth rate (32.54 g m2 day1) at the stage between 6090 days after sowing thereafter they decreased. All the above growth, yield and morphophysiological characters were less effective in BD728. On the basis of these results, BD 725 was found outstanding for plant growth, yield and morphophysiological characters of sorghum. Asian J. Med. Biol. Res. June 2015, 1(2): 271-284